Study of temperature induction to Pseudomonas aeruginosa growth and morphology, the kinetics approach using BPA medium - Masrudin, Ahmad Akhmal (2017)
Environmental pollution is getting worse day by day without no promising solution to control it. Although there are various methods available, microbial degradation pathway looks promising thus more studies needs to be done on it. P. aeruginosa ability to degrades BPA has been studied before and this study is focusing on temperature which this species works best. In this report, the temperature effect on P.aeruginosa was studied along with its kinetic in order to find the best temperature that gives the highest degradation of BPA. Temperature parameter was controlled at 30, 40, 50⁰C. The results show us that this species is a gram-negative monoflagellated bacterium which release pyocyanin pigment, it was able to degrade 72% of BPA from its initial concentration of 4ppm in 24 hours with the rate of 8.42x10¯⁹g/s.